BODY SIZE VARIATIONS OF DAPHNIA CUCULLATA SARS IN A RESERVOIR (ELAZIG-TURKIYE) - Bulut, H.; Saler, S. (Aloki Applied Ecological Research and Forensic Inst Ltd, 2024)
Daphnia cucullata is one of the most abundant zooplankton species, found in 85 percent of freshwater and as a model aquatic organism it was chosen from this study. That is why this zooplankton species was chosen. The plankton samples were collected from Keban Reservoir from 2020-2023 with a standard plankton net (55-mu m mesh size) at the designated station, Plankton samples were stored in 4% formaldehyde solution. Some water quality parameters were determined by making instant physical measurements with a YSI (EXO 2) model device. Water temperature, pH, electrical conductivity, dissolved oxygen, turbidity (Secchi Disk Depth) and Chlorophyll a were measured. In this study, the fouryear body changes of D. cucullata in August from 2020 to 2023 were monitored. During four years of progressive eutrophication in Keban Reservoir, we found that among the five morphological parameters analyzed in D. cucullata length of head, carapace length, length of tail spine, body length, width of carapace had a tendency to decrease.
Keywords: Daphnia cucullata; reservoir; morphology; water quality; T & uuml;rkiye